Separation technology for resource recovery - Lee, Yun Ying (Nanyang Technological University, 2021)
With the rise in the number of urban cities around the world, there is also a corresponding increase in the demand for both resources and water. The increased demand and consumption of such resources would lead to a corresponding increase in waste generated. Wastewater, in particular, needs to be properly treated to prevent the negative impacts that it may bring such as water pollution or eutrophication. Domestic wastewater is known to have high quantities of Nitrogen, which also serves as a key resource in aiding the growth of crops in the agricultural industry. This project explores the possibility of the recovery of N − NH4 in wastewater through the use of electrodialysis to become a phosphate mineral known as Struvite. The formation of Struvite using N − NH4 in wastewater was explored synthetically in 3 stages: (1) increasing the concentration of N − NH4+ in wastewater; (2) increasing the pH of concentrated solution till pH 9.5; and (3) external addition of PO43−as KH2PO4 and Mg2+ as brine. Results have shown that the formation of Struvite was successful, but it was only successful under high concentrations of N − NH4+and would require a concentration factor of about 10 times. Stage 1 (increasing the concentration of N − NH4+in wastewater) proved to be the most crucial step in the formation of Struvite. If concentrations of N − NH4+ were not high enough, Struvite formation would not be significant. There was seen to be a 3-fold increase in the concentration of N − NH4+ during the electrodialysis process of stage 1, done with a concentration factor of 15 times. The energy consumption for such stage 1 was calculated to be about 14.69kWh/Kg N − NH4.